## -(3z + 4) = 6z – 3(3z + 2) Please help and show work!!

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

Lorem ipsum dolor sit amet, consectetur adipiscing elit.Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu.Fusce viverra neque at purus laoreet consequa.Vivamus vulputate posuere nisl quis consequat.

## Answers ( No )

-3z – 4 = 6z – 9z – 6

-3z – 4 = -3z -6

0 = -2

no solution.Equation step-by-step:-(3z + 4) = 6z – 3(3z + 2) → we break down the () with the distributive property

-3z – 4 = 6z – 9z – 6 → we take -4 to the right side of the equation

-3z = 6z – 9z – 6 + 4 → we solve for – 6 + 4

-3z = 6z – 9z – 2 → we solve 6z – 9z

-3z = -3z – 2 → we take -3z to the left side of the equation

-3z + 3z = -2 → we solve for – 3z – 3z

0 = -2 → final answer. There is no solution to this equation, it’s false.Hope it helped,

BioTeacher101